A CRITICAL REVIEW ON DANTAHARSHA IN SHALAKYATANTRA (International Journal of Ayurveda and Pharma Research, 2020)
Mukha is considered as one of the Nava dwaras. Danta is the Anga (part) of Mukha. There are various diseases affecting the Mukha and their Angas. As preventive therapy our Acharyas have mentioned Kavala, Gandusha, Dantadhavan, Mukhaprakhalana etc in Dincharya. One who does not indulge in such regimen is sure to be affected by the diseases of the Mukha.Dantaharsha is one of the 8 Dantaroga explained by Acharya Sushruta and it is the most common disorder of the mouth. Clinically, if teeth do not tolerate cold or heat or any other kind of touch, it is known as Dantaharsha. It can be compared with dental hypersensitivity. Several people all around the world experience this painful condition and are highly prevalent in the adult populations. Dantagatharogas, its causes, prevention and treatment are explained in detail in all the ancient texts of Ayurveda. This shows the importance given to oral health during those eras and even now, it is rightly said oral health is equal to overall health. Many remedies are prescribed in modern medicine for the treatment of dentine hypersensitivity like use of fluorides, oxalates etc in the form of paste, lasers etc. But these methods are quite expensive and often recurrence of the symptoms is seen. Long use of these are said to cause allergic reaction to gums. So it becomes relevant to develop an easy, economic, non toxic and approachable modality as a treatment measure in Dantaharsha.